TARIYXĺY SHĺNLĺQTĺ IMITACIYALAWDA MUZEY EKSPONATLARĺNĺŃ ÁHMIYETI - Seyfullaev, A.S. (SCIENCE and SOCIETY, 2023)
The article says that museums are of great importance in imitating historical reality, in developing historical knowledge and historical thinking through unique exhibits.